(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2010)
This study was carried out in the outpatient unit of the Teaching Hospital of the University of São Paulo (USP), and studied the impact of an educational program aimed at improving hypertensive patients' compliance to treatment. Seventy five (75) hypertensive patients of both sexes took part in the study which had no age or race discrimination. Participants presented no other concomitant pathology, except obesity, diabetes and dyslipidemia. Forty one patients were allocated to an experimental group (EG). Experimental patients attended lectures on the use of medication and artery hypertension (AH) and received personal pharmaceutical guidance for nine months. The control group (CG) comprised 34 patients who did not attend lectures or receive pharmaceutical advice in this period. The results were assessed by means of serum levels of cholesterol and fractions of tryacylglicerol (TG), urine sodium and potassium, arterial pressure (AP), body mass index (BMI), waist-hip ratio (WHR), and also based on responses to a questionnaire focusing on AH and treatment. Patients who received the guidance showed a greater decrease in AP, TG and WHR, besides an increase of potassium excretion through urine. The experimental group also scored higher on the questionnaires compared to the CG. It was concluded that the educational process, applied under the conditions of the present study, improves clients' clinical response to antihypertensive treatment and should be included in therapeutic strategies of health care services dealing with hypertensive patients.